Implementation of Integrated Science Model With Audiovisual Teaching Materials To Improve Students’ Learning Outcomes and Science Process Skills - Emilia Candrawati; Sumpono; Agus Sundaryono; Mellyta Uliyadari (IJORER : International Journal of Recent Educational Research, 2020)
This study aims to determine the effectiveness of the integrated science learning type connected to achieving basic competencies and improving science process skills. This study uses a 4-D development model that is defined, design, develop, and disseminate with one-group posttest design implemented in 5th-semester students of Chemistry Education, University of Bengkulu. The research instrument is a posttest question to measure learning outcomes and observation sheets to measure science process skills. The teaching materials used are sourced from part of the process and the results of the activity test of palm oil endophytic bacteria ethyl acetate extract against Fusarium oxysporum f.sp. by TLC-bioautography is packaged in the form of learning videos. The results showed that the Integrated Science type of Connected model was used effectively to improve student learning outcomes and science process skills.